2007
DOI: 10.1300/j229v08n03_03
|View full text |Cite
|
Sign up to set email alerts
|

Ethics of Asking Trauma-Related Questions and Exposing Participants to Arousal-Inducing Stimuli

Abstract: This study examined ethical concerns related to exposing participants with childhood victimization histories to both trauma-specific and non-trauma-specific stimuli. We asked participants questions about childhood victimization experiences and exposed participants to a negatively-arousing experimental condition. Following each of these procedures and at a one-week follow-up session, participants completed a measure designed to asses their reactions to participation. The measure included several questions to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…However, extent of exposure was positively associated with distress for research samples comprised of participants who have a history of exposure to mass disaster, domestic violence, and other interpersonal trauma (Black et al, 2006;Boscarino et al, 2004;Galea et al, 2005;Johnson & Benight, 2003;Newman et al, 1999;Walker et al, 1997). Among college students, trauma history was unrelated to (Cromer et al, 2006, Sample 2, p. 350;DePrince & Freyd, 2004), positively correlated with (Cartier-Visscher, Naugle, Bell, & Suvak, 2007;Cromer et al, 2006, Sample 1, p. 350;Edwards et al, 2009), and negatively correlated with distress across studies (Newman et al, 2001).…”
Section: B E N E F I C E N C E a N D N O N M A L E F I C E N C Ementioning
confidence: 99%
“…However, extent of exposure was positively associated with distress for research samples comprised of participants who have a history of exposure to mass disaster, domestic violence, and other interpersonal trauma (Black et al, 2006;Boscarino et al, 2004;Galea et al, 2005;Johnson & Benight, 2003;Newman et al, 1999;Walker et al, 1997). Among college students, trauma history was unrelated to (Cromer et al, 2006, Sample 2, p. 350;DePrince & Freyd, 2004), positively correlated with (Cartier-Visscher, Naugle, Bell, & Suvak, 2007;Cromer et al, 2006, Sample 1, p. 350;Edwards et al, 2009), and negatively correlated with distress across studies (Newman et al, 2001).…”
Section: B E N E F I C E N C E a N D N O N M A L E F I C E N C Ementioning
confidence: 99%
“…Such ramifications can also influence consent to assessment and treatment (Carter-Visscher et al 2007). Maltreated youth may also be less likely to speak to an assessor about their trauma in the presence of a parent.…”
Section: Assessmentmentioning
confidence: 99%
“…Uniformly, such studies have reported that a majority of participants with PTSD report minimal distress in response to questions about their traumatic experiences or about their PTSD symptoms, and findings are robust across diverse measures of reactions to research participation and study modalities (e.g., mailed surveys, psychophysiological evaluation of distress, and interviews that included direct inquiry about prior trauma exposure; Griffin et al 2003;Walker et al 1997). Although participants may report some distress in response to answering trauma-specific questions, such distress does not seem to have residual effects (e.g., Carter-Visscher et al 2007). Further, other studies provide evidence that distress associated with trauma-focused research was also found in participants who lack trauma exposure (i.e., controls) (Edwards et al 2009).…”
Section: Beneficence and Nonmaleficencementioning
confidence: 82%
“…At least one study has highlighted a link between levels of current PTSD symptoms and past trauma with greater distress during traumafocused research participation (Carlson et al 2003). Additional participant characteristics that have been associated with higher levels of distress during research participation include: (a) intensity of past trauma exposure, with greater intensity associated with greater propensity for upset; (b) early exposure to trauma (e.g., childhood abuse, childhood traumatic exposure); and (c) poor coping selfefficacy (Carlson et al 2003;Carter-Visscher et al 2007;Johnson and Benight 2003;Parslow et al 2000;Walker et al 1997).…”
Section: Beneficence and Nonmaleficencementioning
confidence: 99%
See 1 more Smart Citation